How to Avoid Taxes How to Avoid Taxes: The Role of Firm Size in Indonesian Food and Beverage Companies - Purba, Pebisitona Mesajaya; Sumiok, Cristofer; Evinita, Lenny Leorina; Wuryaningrat, Nikolas F.; Purba, Dimita H. P. (Jurnal Akuntansi Manado (JAIM), 2025)
This study looks at how profitable, liquid, and solvent a company is and how that affects its decision to avoid taxes. We focused on companies in the food and beverage sector that are listed on the Indonesia Stock Exchange from 2020 to 2023. We used a statistical method to analyze the data. The results showed that profitability has a significant negative effect on tax avoidance, while liquidity has a significant positive effect. Solvency and company size directly show no significant effect. However, as a moderating variable, company size strengthens the effect of liquidity and solvency on tax avoidance, and weakens the effect of profitability. The control variables capital intensity and inventory intensity consistently show a significant negative effect on tax avoidance. These findings suggest that large companies with high profits usually comply with taxes, while those with high liquidity and solvency are more likely to avoid taxes.